Pemanfaatan cairan limbah penggaraman ikan Patin sebagai bahan pembuatan kecap - Restu Restu (JURNAL ILMU HEWANI TROPIKA (JOURNAL OF TROPICAL ANIMAL SCIENCE), 2017)
Fish sauce is one of traditional fishery products mixed by fermentation from extract of fish flesh that is a byproduct of processing fish. The results of the study showed that liquid product of the process salting for ± 24 hours in the phase of processing wadi of catfish can be used as material for making fish sauce. The fish sauce product from catfish ( Pangasius sp ) fulfill with Indonesia National Standard criteria : looking clear, specific smell and taste of fish sauce, pH 5,09 - 5,53; and organoleptic value (7,26) with criteria enough favored by the the panel.